Preparation and Pyrolysis Kinetics of Polyester-Based Waterborne Polyurethanes with High Solid Content - Feng, Jianyan; Luo, Xiaomin; Yang, Feifei; Wang, Xuechuan (Asian Journal of Chemistry, 2015)
The waterborne polyurethane emulsion with a solid content 51.43 wt % was prepared by using main raw materials comprising polyester polyol, isophorone diisocyanate and 2,2-dimethylol propionic acid. The relationship between the particle size distribution and the maximal volume fraction of dispersed phase of the waterborne polyurethanes was simulated through a mathematical model of close packing of sphere particles. The emulsion structure and properties of the resulting emulsion films were characterized by a Fourier transform infrared spectroscopy, a laser particle size analyzer, a universal testing machine, a contact angle meter. The thermal decomposition process of the waterborne polyurethanes was analyzed by a thermal gravimetric analyzer. According to using simulations of Kissinger’s, Ozawa’s and Crane’s methods, the activation energy, the reaction order and the frequency factor of the thermal decomposition process of waterborne polyurethanes were calculated as 116.097 kJ/mol, 0.911, 1.963 × 107 s-1, respectively. Besides, the high-solid-content waterborne polyurethane with a viscosity of 316 mPa·s was found to exhibit a wide particle size distribution, a good water resistance and excellent mechanical properties.